2007
DOI: 10.1902/jop.2007.070160
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Er,Cr:YSGG Laser Irradiation on the Root Surface: Morphologic Analysis and Efficiency of Calculus Removal

Abstract: Based on these findings, it is appropriate to use a 1.0-W power output setting with an Er,Cr:YSGG laser for root scaling. This may be done without any conspicuous morphologic alterations to the root surface and with acceptably efficient removal of calculus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
55
0
12

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 36 publications
9
55
0
12
Order By: Relevance
“…These characteristics are consistent with those observed in other in vitro studies that evaluated the morphology of dentin irradiated with Er:YAG 4,8,11 and Er,Cr:YSGG lasers. 7,9,12,13 The morphological characteristics of the surfaces irradiated with these lasers are explained by the laser tissue ablation mechanism, called photomechanical ab- …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These characteristics are consistent with those observed in other in vitro studies that evaluated the morphology of dentin irradiated with Er:YAG 4,8,11 and Er,Cr:YSGG lasers. 7,9,12,13 The morphological characteristics of the surfaces irradiated with these lasers are explained by the laser tissue ablation mechanism, called photomechanical ab- …”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that irradiation of root surfaces using Er:YAG lasers does not promote the formation of a smear layer. 4,7 Additionally, the Er:YAG and ErCr: YSGG lasers promote a selective removal of calculus with minimal damage to root surfaces, [8][9][10] and may be clinically effective for stabilizing the clinical parameters of periodontal disease. 2,3 Although the Er:YAG 1 and Er,Cr:YSGG 3 lasers have been recommended for root instrumentation, to our knowledge there are no studies reporting a direct comparison between these tools.…”
Section: Introductionmentioning
confidence: 99%
“…Son zamanlarda erbium katkılı itriyum alümin-yum garnet laser (Er:YAG) ile çok daha olumlu sonuçlar alınmıştır. Subgingival diştaşları ablete edilerek uzaklaştırılmakta, periopatojen bakteriler elimine edilmekte, hatta sement yüzeyindeki lipopolisakkarit yapısındaki endotoksinler de inaktive edilmektedir [22][23][24][25][26] . El aletleriyle ve laser ile yapılan SRP işlemleri karşılaştı-rıldığında; laserin kök yüzeyini daha fazla pürüzlen-dirdiği, geride hiç smear tabakası bırakılmadığı, kan komponentlerinin ve fibroblastların yüzeye adezyonunu kolaylaştırdığı ve böylece rejeneratif tedaviyi kolaylaştırdığı gösterilmiştir [24][25] .…”
Section: Ultrasonik Ve Sonik Aletlerle Yapılan Diş Taşı Temizliği Ve unclassified
“…The Er:YAG laser has been shown, in vitro, to remove calculus 12 and to negate endotoxin. 12,15,24,25 There is the potential for root surface damage during the process of in vivo calculus removal since the Er:YAG is a hard tissue laser and the operator would not be able to visualize what is being lased. Clinical data on attachment level changes when compared to SRP alone are conflicting, with some studies showing a slight benefit while others show no benefit.…”
Section: Laser-mediated Sulcular And/or Pocket Debridementmentioning
confidence: 99%